Healthy Lifestyle, Coping, and Adaptation of Public Health Nurses Amidst COVID-19 Pandemic in Selected Municipalities of Isabela Basis for Wellness Intervention Program - Erika Jasmin O. Erika; Kimberly Blando; Katrina A. Grapa; Jonalyn E. Limon; Candice Caronina P. Claraval; Rianne Maie C. Mangaoil (Jurnal Keperawatan Respati Yogyakarta, 2023)
Considering the struggles with this kind of situation, the COVID-19 pandemic restored the appreciation for healthy lifestyle behaviors as well as the coping and adaption techniques of Public Health Nurses (PHNs). The study assessed the PHNs' coping, adaptation, and healthy lifestyle practices; the significant relationship between their healthy lifestyle practices and coping and adaptation styles based on their profile; and the possible need to intervene based on the results of the study through a wellness intervention program. Descriptive-correlational study was conducted in the adopted municipalities from the southern part of Isabela namely Echague and Alicia, through a survey method. The study's findings suggest that PHNs' healthy lifestyle behaviors, as well as their coping and adapting techniques, were effective throughout the onset of COVID-19. Furthermore, the findings revealed that older respondents (36-50 years old) are more likely to follow healthy lifestyle practices in the domain of nutrition (M = 4.15), whereas married respondents (M = 3.66) are more likely to engage in physical activity on a regular basis than their younger counterparts. In comparison to contractual employees, permanent employees with an average of (M = 4.19) are more conscious of their role function as part of their coping and adapting to the COVID-19 pandemic. Finally, the association between respondents' healthy lifestyle, coping, and adaption approaches demonstrates a substantial positive relationship, particularly in terms of nutrition and physiologic adaptation with an r-value of 0.745 at a 0.001 p-value, physical activity and physiologic mode with an r-value of 0.669 at a 0.001 p-value, and physiologic mode and stress management with an r-value of 0.655 at a 0.001 p-value. Moreover, the domains of stress management and self-concept mode also show a strong positive relationship with an r-value of 0.698 at a 0.001 p-value.